Clinical characteristics of sarcoidosis patients in Belgium. Issue 2 (4th March 2022) - De Ridder, Jolien; Ronsmans, Steven; Vanderschueren, Steven; Wuyts, Wim; Yserbyt, Jonas
ABSTRACT: Background: Sarcoidosis is a non-caseating granulomatous disease, mostly affecting previously healthy persons in their fourth and fifth decade. In Belgium, there is a paucity of epidemiological data concerning sarcoidosis and it is unknown to what respect national data on sarcoidosis relates to the global epidemiology of the disease. Objectives: In this cohort study we describe the patient population in an academic center of reference, serving both as a regional care center and a center for a tertiary referral. Methods: We collected epidemiological data among 234 consecutive patients consulting the outpatient sarcoidosis clinic during a two-year time period. We manually explored the electronic patient file for data retrieval. Results: Out of the 234 patients, 140 are male (60%) and 94 are female (40%) patients. Forced vital capacity showed a median decline of 2% during follow-up, whereas median diffusion capacity increased with 4% over the same period of time. Within our study cohort, we observed a preponderance in employment as construction workers (14%), the chemical industry (6%) and in the metal processing industry (6%). Conclusion: The current study reports on epidemiological findings among the largest cohort of sarcoidosis patients in Belgium published to date. Graphical abstract uf0001